A novel non-integrative single-cycle chimeric HIV lentivector DNA vaccine. Issue 19 (5th May 2015) - Moussa, Maha; Arrode-Brusés, Géraldine; Manoylov, Iliyan; Malogolovkin, Alexander; Mompelat, Dimitri; Ishimwe, Honorine; Smaoune, Amel; Ouzrout, Bilel; Gagnon, Jean; Chebloune, Yahia
Abstract: Novel HIV vaccine vectors and strategies are needed to control HIV/AIDS epidemic in humans and eradicate the infection. DNA vaccines alone failed to induce immune responses robust enough to control HIV-1. Development of lentivirus-based DNA vaccines deficient for integration and with a limited replication capacity is an innovative and promising approach. This type of vaccine mimics the early stages of virus infection/replication like the live-attenuated viruses but lacks the inconvenient integration and persistence associated with disease. We developed a novel lentivector DNA vaccine "CAL-SHIV-IN − " that undergoes a single round of replication in the absence of integration resulting in augmented expression of vaccine antigens in vivo . Vaccine gene expression is under control of the LTRs of a naturally attenuated lentivirus, Caprine arthritis encephalitis virus (CAEV) the natural goat lentivirus. The safety of this vaccine prototype was increased by the removal of the integrase coding sequences from the pol gene. We examined the functional properties of this lentivector DNA in cell culture and the immunogenicity in mouse models. Viral proteins were expressed in transfected cells, assembled into viral particles that were able to transduce once target permissive cells. Unlike the parental replication-competent SHIV-KU2 that was detected in DNA samples from any of the serial passage infected cells, CAL-SHIV-IN − DNA was detected only in target cells of the first round of infection, hence demonstrating the single cycle replication of the vaccine. A single dose DNA immunization of humanized NOD/SCID/β2 mice showed a substantial increase of IFN-γ-ELISPOT in splenocytes compared to the former replication and integration defective Δ4SHIV-KU2 DNA vaccine.